Zinc methionine and laminarin have growth‐enhancing properties in newly weaned pigs influencing both intestinal health and diarrhoea occurrence. Issue 6 (18th November 2016) - Bouwhuis, M. A.; Sweeney, T.; Mukhopadhya, A.; Thornton, K.; McAlpine, P. O.; O'Doherty, J. V.
Summary: Three experiments were conducted to investigate the interaction between zinc methionine (ZnM) and laminarin (LAM) on piglet growth performance and intestinal health post‐weaning. Experiment 1 was designed as 2 × 2 factorial with four treatments [ n  = 8, weaning age (WA) 24 days, live weight (LW) 7.15 kg]: (i) basal diet (BD); (ii) BD + 500 mg/kg ZnM; (iii) BD + 300 mg/kg LAM; and (iv) BD + 500 mg/kg ZnM + 300 mg/kg LAM. There was an interaction (p < 0.05) between LAM and ZnM. Pigs that were offered the LAM diet had a similar performance to the BD. However, when combining LAM with ZnM, pigs had reduced average daily gain (ADG), gain‐to‐feed ratio (G:F) and LW at slaughter at day 8 post‐weaning compared to the ZnM. Both LAM and ZnM improved the small intestinal morphology of the pigs at day 8 post‐weaning. Experiment 2 was designed as 2 × 2 factorial with four dietary treatments ( n  = 9, WA 24 days, LW 7.32 kg): (i) BD; (ii) BD + 500 mg/kg ZnM; (iii) BD + 175 mg/kg LAM; and (iv) BD + 500 mg/kg ZnM + 175 mg/kg LAM. The ADG and average daily feed intake were improved between day 0 and 31 PW when pigs were offered a LAM diet (p < 0.01). Faecal scores were reduced between day 0 and day 31 post‐weaning with ZnM (p < 0.001). Experiment 3 consisted of four dietary treatments ( n  = 10, WA 24 days, LW 7.32 kg): (i) BD; (ii) BD + 3300 mg/kg zinc oxide (ZnO); (iii) BD + 500 mg/kg ZnM; and (iv) BD + 175 mg/kg LAM. Pigs that were offered the ZnO diet had an increased ADG compared to the BD or ZnM diets (p < 0.01). Pigs that were offered the LAM diet had increased ADG compared to the ZnM diet (p < 0.05). Faecal scores were reduced between day 0 and day 31 PW with ZnM or ZnO supplementation (p < 0.001). In conclusion, the inclusion of 175 mg/kg LAM and ZnO improved ADG while both ZnO and ZnM reduced the faecal scores post‐weaning.